Industrial Cluster Learning - Purwaningsih, Isti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2003)
Globalization impact and economics crisis in Indonesia has been changed Indonesiaeconomics structure. Many manufacture industries have been shut down, especially which issupported by imported raw material. This is certainly a very clear proof that our industrialfoundation is not rigid. Goverment has changed industrial development strategy into industrialcluster approach to survive this crisis. There are 3 model to analyze industrial cluster, i.e. CollectiveEfficiency, Flexible Specialization, and Porter Diamond Model. This research was focused on studying industrial cluster, with case study on tennagemanufacture in Yogyakarta, based on Porter Diamond Model. Porter Diamond Model consist of four determinant, i.e. (1) factor conditions, (2) demand condition, (3) firm strategy, structure, andrivalry, and (4) related and supporting industry.